Iraq's Oil Exports for 2023: Time Series Analysis: Ekspor Minyak Irak untuk tahun 2023: Analisis Deret Waktu - Mhfoudh Falih Hasan; Afnan Ahmed Abd Ali; Mayada Rashied Kamil (Universitas Muhammadiyah Sidoarjo, 2024)
Crude oil is a vital energy source due to its high thermal energy output and lower cost compared to other energy sources. This study aimed to identify key variables influencing Iraq’s oil revenues through a descriptive and analytical examination of Iraq’s oil exports in 2023. Data showed monthly fluctuations in the average price and quantity of crude oil exported, with prices ranging from 71.485 to 91.353 per barrel, reflecting a 7.5% increase compared to the previous year. An inverse relationship was observed between oil prices and export volumes, where higher prices typically increased production and exports, while lower prices reduced them. The findings highlight Iraq's heavy reliance on oil exports, exposing its economy to risks from fluctuating oil prices, deteriorating infrastructure, environmental restrictions, and international regulations. The study concluded that diversifying the economy and addressing these challenges is crucial. It recommends improving infrastructure by modernizing ports, roads, railways, and oil facilities while enhancing security measures to support the oil sector and reduce vulnerabilities. Highlights: Crude oil drives Iraq's economy but risks dependency vulnerabilities. Oil prices fluctuated in 2023, impacting production and export levels. Modernize infrastructure and secure facilities to stabilize oil exports. Keywords: Iraq, Oil Exports, Time Series Analysis